Digital Media, Creativity, Narrative Structure and Heritage - Tara Copplestone; Daniel Dunne (Internet Archaeology, 2017)
Media forms, digital creativity and narrative structure have a reflexive relationship to the narratives they portray. Digital media combined with creativity facilitate a wide range of narrative structures, many of which are digitally specific, beyond the norm of traditional displays. However, many of the heritage outcomes we observe through digital media employ narrative structures that do not make use of the specifically digital affordances.